Historical Development and Practices of Lawns in China. (1st February 2019) - Yang, Fengping; Ignatieva, Maria; Larsson, Anders; Xiu, Na; Zhang, Shuoxin
Abstract : Lawn, the most common human-created and culture-shaped habitat in urban green areas, has recently been questioned because of the negative environmental impacts from intensive lawn management. China, a late adopter of lawns, has a great potential to implement sustainable lawns. Based on a literature review, field observations and interviews with local politicians, lawn managers, landscape architects and local residents in Chinese cities, this study seeks inspiration for sustainable lawns within classical Chinese gardening and European examples and identifies the drivers of lawn development in China. The definition of lawns has varied over time, evolving with the changes in the relationship between human and environment. Chinese people's paradigm on lawns is influenced by the trend of Westernisation and globalisation after 1840s. We conclude that shifting the existing paradigm to environmentally friendly lawn aesthetics and bridging the knowledge gap between researchers and practitioners are challenges in achieving sustainable lawns in China. This paper creates a better understanding of the lawn phenomenon in China and is one step ahead in shifting people's paradigm of lawns in countries that are later adopters of lawns.